FRAMING PIDATO PRESIDEN JOKO WIDODO PADA PEMBUKAAN IMF 2018 DI KOMPAS.COM DAN SUARA.COM - Irma Yuni Arti Manalu; Sholihul Abidin (PROGRAM STUDI ILMU KOMUNIKASI, 2020)
Game of Throne analogy of the opening speech of the 2018 IMF by President Joko Widodo raises the pros and cons of political opponents. Many mass media reported how the contents of the speech delivered by President Joko Widodo were both from the pros and the cons. Every mass media has a certain point of view in every news that is done for an issue. The mass media that functions to oversee the government and spread information and become control of power. The research method used is interpretative qualitative with Robert N. Entman's framing analysis technique models that define problems, diagnose causes, make moral judgment, and treatment recommendations. Kompas.com and Suara.com placed the opening speech of IMF President Joko Widodo, appreciation from various groups and criticism from political opponents as important events in the news. However, from each of these events, the value of the moral message contained in President Joko Widodo's speech was more important as an event by the two media so that the value was continuously conveyed in the news. In reporting the opening speech of President Joko Widodo's IMF in 2018, the reality of the media constructed by kompas.com and Suara.com showed the partiality of the two media to President Joko Widodo rather than the counter parties to the opening speech.